Accelerating Progress towards Reaching Sustainable Development Goals - Baral, Kedar Prasad; Yadav, Uday Narayan; Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2018)
There is time bond succession from Millennium Development Goals to Sustainable Development Goals from 2015 as a defined point of demarcation. This is an ultra short sociopolitical intervention in order to transform society into a healthier state. This is an unnatural process that depends on will and resources. As the country is in political transition it would be an opportunity to assure to implement programs and plans early ahead.